2013
DOI: 10.3109/13561820.2013.851073
|View full text |Cite
|
Sign up to set email alerts
|

The (stalled) progress of interprofessional collaboration: the role of gender

Abstract: Researchers have demonstrated that team-based, collaborative care improves patient outcomes and fosters safer, more effective health care. Despite such positive findings, interprofessional collaboration (IPC) has been somewhat stunted in its adoption. Utilizing a socio-historical lens and employing expectation states theory, we explore potential reasons behind IPC's slow integration. More specifically, we argue that a primary mechanism hindering the achievement of the full promise of IPC stems not only from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 33 publications
4
53
0
3
Order By: Relevance
“…The field of medicine continues to be predominantly male (66 percent men, 33 percent women) [7], while the field of nursing continues to be predominantly female (91 percent women, 9 percent men) [8]. Gender underrepresentation in medicine (for women) and nursing (for men) can be sources of ineffective or fragmented interprofessional patient care, perhaps due to power differentials rooted in each field's historically situated hierarchies and gender dynamics [9]. Adding to this, in the US health care system, physicians provide billable services, which create revenue, whereas nursing services-depending on the level of care-are not always billable [10,11].…”
Section: Current Challenges For Interprofessional Collaboration In Admentioning
confidence: 99%
“…The field of medicine continues to be predominantly male (66 percent men, 33 percent women) [7], while the field of nursing continues to be predominantly female (91 percent women, 9 percent men) [8]. Gender underrepresentation in medicine (for women) and nursing (for men) can be sources of ineffective or fragmented interprofessional patient care, perhaps due to power differentials rooted in each field's historically situated hierarchies and gender dynamics [9]. Adding to this, in the US health care system, physicians provide billable services, which create revenue, whereas nursing services-depending on the level of care-are not always billable [10,11].…”
Section: Current Challenges For Interprofessional Collaboration In Admentioning
confidence: 99%
“…These inequalities of professional culture and stereotypes have been highlighted in more recent research regarding the education of medical and nursing students, as affecting how students look upon themselves, their future profession, collaboration and professional practice (Wilhelmsson, Ponzer, Dahlgren, Timpka, & Faresjö, 2011). The same principles though are expected also to apply to other health care professionals (Bell, Michalec & Arenson, 2014). Hofseth et al (2010), have argued that professional cultures seem to reflect social class, power and gender issues.…”
Section: Professions and Professionalsmentioning
confidence: 99%
“…That kind of practice arrangement may lead to questions on how the students perceived professional cultures and stereotypes. Previous studies have shown that educational experiences and socialisation processes during training and professional practice reinforce professional stereotypes and cultures, which then become barriers to a successful IPC (Bell et al, 2014;Hall, 2005;Mandy, Milton & Mandy, 2004).…”
Section: Interprofessional Legitimacy and Powermentioning
confidence: 99%
See 2 more Smart Citations